Use of venography including the dorsal 60° proximal‐palmaro‐/plantaro‐distal oblique to improve the evaluation of nonlaminitic digital disease of the horse. (30th September 2021) - Trolinger‐Meadows, K.; Morton, A.; McCarrel, T.; Porter, E.; Dryden, V.
Summary: Background: Many common nonlaminitic conditions of the equine digit can be diagnosed radiographically, although vascular disturbance cannot be evaluated without use of contrast venography. Digital venography is commonly used to assess vascular disturbance in horses with laminitis. Routine venography projections include the lateromedial (LM) and dorsopalmar/dorsoplantar (DP) projections, although these do not provide complete assessment of the digital vasculature. Objectives: The purpose of this study was to describe digital venography as a diagnostic tool for nonlaminitic disease of the digit of horses including the dorsal 60° proximal‐palmaro‐/plantaro‐distal oblique (60° DP) in addition to the standard LM and DP projections. Study design: Retrospective descriptive case series. Methods: Medical records were reviewed to identify patients with nonlaminitic disease that had digital venography including LM, DP and 60° DP projections. Horses free of disease of the digit were utilised for comparison. Images were reviewed, and presence or absence of radiographic and venographic abnormalities was determined individually. Results: Venography revealed vascular abnormalities in horses with digital keratoma, complex digital abscessation and simple digital abscessation. The inclusion of the 60° DP projection allowed for better determination of the location and extent of vascular disturbance of the distal phalanx. Main limitations: Limitations of the study include the small sample size and retrospective nature, as well as lack of literature describing vascular disturbances in nonlaminitic processes. Conclusions: Digital venography can be considered for evaluation of submural disease of the digit of horses. For more complete assessment of the distal phalangeal vasculature, the 60° DP projection should be included in all digital venographic studies.